ANALISIS CITIZEN E-READINESS DALAM PENGEMBANGAN DESA BERBASIS TEKNOLOGI INFORMASI - Susanto, Anton (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2011)
Development of e-government services for rural communities become more important for succeed many government programs. Citizen e-readiness should be evaluated to measure the capability and awareness of rural society. with Information and Communication Technology (ICT). This research attempt to measure citizen e-readiness by focusing in 5 factors, that are human resources, culture in !CT-adoption, ICT-Infrastructure, business climate and income. Research was carried out by case study in Terong, one of the villages in Bantul, Yogyakarta. This research found that human resources, culture and business climate factors have level of e-readiness higher than level of e-readiness in infrastructure and income factors. And it indicates the need of more actions to increase the e-readiness of priority factors.